The mediation effect of social support between stigma and social alienation in patients with stroke - Wu, Yu; Yan, Zeping; Fornah, Lovel; Zhao, Jun; Wu, Shicai (Frontiers in Public Health, 2023)
Background: Social alienation is prevalent and causes adverse outcomes in stroke. Previous studies have linked stigma with social alienation. However, little is known about the mechanisms behind this relationship. This study explored the mediation effects of social support between stigma and social alienation. Methods: A cross-sectional design was used to study 248 patients with stroke admitted to a tertiary rehabilitation hospital in Beijing, China, from December 2022 to July 2023. Patients were assessed using a general information questionnaire, the Stroke Stigma Scale, the Social Support Rating Scale, and the Generalized Social Alienation Scale. The PROCESS macro in SPSS was used to examine the mediation model.The results showed that stigma has a negative effect on social support (β=-0.503, P ＜ 0.001); stigma has a positive effect on social alienation (β=0.768, P ＜ 0.001). Social support mediated the relationship between stigma and social alienation, with a mediation effect of 0.131 (95%CI: 0.060, 0.214), and indirect effects accounted for 17.06% of the total effect. Conclusions: Social support mediated the relationship between stigma and social alienation. These findings suggest that intervention targeting the enhancement of social support may prevent or reduce social alienation among patients with stroke.